Supply chain management and corporate governance : artificial intelligence, game theory and robust optimisation - Lou, Catherine Xiaocui; Islam, Sardar M. N., 1950-; Billington, Nicholas (Routledge studies in corporate governance., 2023)
"Supply Chain Management and Corporate Governance: Artificial Intelligence, Game Theory and Robust Optimisation is the first innovative, comprehensive analysis and analytical robust optimisation modelling of the relationships between corporate governance principles and supply chain management for risk management and decision making under uncertainty in supply chain operations. To avoid corporate failures and crises caused by agency problems and other external factors, effective corporate governance mechanisms are essential for efficient supply chain management. This book develops a new collaborative robust supply chain management and corporate governance (RSCMCG) model and framework that combines good corporate governance practices for risk management strategies and decision making under uncertainty. This model is developed as a principal agent game theory model, and it is digitalized and computed by Excel algorithms and spreadsheet as an artificial intelligence and machine learning algorithm. The implementation of the SCMCG model provides optimal supply chain solutions, corporate governance principles, and risk management strategies for supporting the company to achieve longterm benefits in firm value and maximising shareholders' interests and corporate performance while maintaining robustness in an uncertain environment. This book shows the latest state of knowledge on the topic and will be of interest to researchers, academics, practitioners, policymakers, and advanced students in the areas of corporate governance, supply chain management, finance, strategy, and risk management"- Resumé vydavatel